Asuhan Keperawatan Pada Perempuan Dewasa Dengan Diagnosa Gastritis - Mona Ariestia (Jurnal Ilmiah Cerebral Medika, 2019)
Gastritis is an inflammation of the gastric mucosa that is uncomfortable in the upper stomach, nausea, vomiting, decreased appetite, or headaches. Gastritis is one type of case commonly suffered by adolescents, which is caused by various factors including diet or lifestyle and behavior to prevent gastritis. The danger of gastritis if allowed to continue will damage stomach function and can increase the risk of developing gastric cancer and causing death. From the Padang city health office in 2015, gastritis was in the 2nd place after rheumatic disease, namely 13,453 people. At RS.TK III Dr. Reksodiwiryo padang, the incidence of gastritis in 2015 was recorded at around 98 people and an increase in 2016 to 181 people. The purpose of this study was to determine how the application of nursing care to gastritis patients. The research design used is a case study and descriptive research type. The results of the study were found at Ny. S complaints of stomach pain, heartburn, nausea and dizziness. According to the theory, there are as many as four possible nursing diagnoses. In this case three diagnoses were found. The nursing plan was in accordance with the NIC, while the nursing evaluation was in accordance with the NOC where one unresolved diagnosis such as pain and two partially resolved diagnoses were the client's nutritional fulfillment and sleep disorders. Suggestions for the hospital to be able to provide further guidance on the implementation of which pain has not been resolved in gastritis patients.